Econometric analysis of panel data - Baltagi, Badi H. (Chichester, UK ; Hoboken, NJ : John Wiley & Sons, 2008)
This new edition reflects the rapid developments in the field covering the vast research that has been conducted on panel data since its initial publication. Featuring the most recent empirical examples from panel data literature, data sets are also provided as well as the programs to implement the estimation and testing procedures described in the book.
Includes bibliographical references (p. 311-335) and index.
osa 26/04/13
Loans
Keywords: Econometrics; Panel analysis